Potential of sodium dichromate and sodium silicate to control in vitro growth of Bacillus cereus, a metal corrosion-causing bacterium - YENNI CIAWI; FAINMARINAT SELVIANI INABUY; NI MADE TERIYANI; YAN RAMONA (Society for Indonesian Biodiversity, 2023)
Abstract. Ciawi Y, Inabuy FS, Teriyani NM, Ramona Y. 2023. Potential of sodium dichromate and sodium silicate to control in vitro growth of Bacillus cereus, a metal corrosion-causing bacterium. Biodiversitas 24: 1530-1537. The maintenance cost of metal-based objects in industrial and construction sectors has been found to significantly increase due to corrosion. Most corrosion is caused by metal oxidation, and about 2% of this corrosion is induced by microbial activity (MIC). The main objectives of this research were to isolate, and identify corrosion-causing bacteria, and to find out the optimum concentration of sodium dichromate and sodium silicate to control their growth in vitro. These compounds have been used to protect the metal surface from corrosion caused by non-microbial-induced corrosion. Three different bacterial isolates were obtained in this study and the black colony (the predominant isolate) was further investigated in the determination of their optimum inhibitory concentrations. Application of sodium dichromate and sodium silicate at the rates of 0.1% w/v and 2% w/v, respectively were found to be optimum to inhibit the in vitro growth of this black bacterial isolate in our study. The predominant isolate found in our study was identified as Bacillus cereus, following the alignment of its 16s rDNA sequence with those deposited at the GenBank (NCBI). Additionally, Enterobacter asburiae was also found on the surface of corroded water tanks.